"When and how are peritoneal metastases of colo-rectal origin treatable". (August 2022) - Cortés-Guiral, Delia; Alyami, Mohammad
Abstract: Peritoneal metastasis (PM) of colorectal cancer (CRC) origin can be treated and cured. This article presents a practical guide for CRC surgeons facing a patient with PM and presents the different options of treatment at expert centers on peritoneal surface malignancies. The unexpected finding of PM could be overwhelming, especially during an emergency CRC surgery. Clear indications on managing these situations call for clarification to avoid any negative impact on the oncologic outcome of patients with CRC. All patients with PM of CRC origin must be evaluated by a tumor board or multidisciplinary team specialized in the management of peritoneal surface malignancies since currently there are available options of treatment for patients with resectable peritoneal disease, unresectable peritoneal disease, and even patients with synchronous liver metastases (LM) could benefit from a multimodal approach.